The Role of Learning Technology in Encouraging Student Creativity in Foreign Language Learning in Higher Education - Al Malikul IKhwanda Putra; Ali Nasith; Yohana S Touwe; Dahlan Abdullah (Yayasan Adra Karima Hubbi, 2023)
Background. This research analyzes the role of Learning Technology in stimulating student creativity in foreign language learning in higher education. The research background highlights the importance of integrating learning technology in the context of higher education, especially in developing student creativity in foreign language learning. With the rapid development of Learning Technology, this research tries to measure and analyze its impact on student creativity. Purpose. The aim of this research is to identify the extent to which Learning Technology influences the level of student creativity, assess preferences and trends in technology use, and provide recommendations for increasing the effectiveness of technology use in supporting foreign language learning. With a quantitative approach through a survey model, this research combines a comprehensive research design to gain in-depth insights. Method. The research methodology includes creating a questionnaire that reflects key aspects, such as the type of technology used, frequency of use, and perceptions of creativity. Respondents were selected from university students who were actively taking foreign language courses, especially Arabic and English. Distribution of the questionnaire was carried out via Google Forms and WhatsApp groups, ensuring efficient participation. Results. Data analysis using the Miles and Huberman model allows for an in-depth interpretation of the relationship between the use of Learning Technology and the level of student creativity. The research results highlight students' positive views on the impact of creativity generated by the use of learning technology, especially in collaboration and developing speaking and writing skills. Conclusion. This research provides a solid foundation for understanding the role of Learning Technology in shaping students' foreign language learning experiences. These conclusions provide valuable information for higher education institutions and policy makers to continue to improve the integration of learning technology, create an environment that supports creativity, and enrich the foreign language learning process in the future.